(3TQM OjhGf TYQ GdMGOQIs - (3CHi YHO Gddg eMeO Hf GdYHGS Hf eMeO GdjRjOis; (3GdMGOQI , bWHI Hf GhS Hf eMUf Hf LQhd GdeGRfj GdZWaGfj, GdMGOQgs
(3ChdgG (B:s
(3cGfc MGOQI GdefcHjf QUYGA JfbV ai MGR s
(3BNQgG (B:s
(3bGd CHh YHO Gddg GdjRjO Yf GHf GdCYQGHi bGd SeYJ CYQGHjkG jbhd hEf TQ GdZHjGJ ZHjI GdfHd Je TYQ GdMGOQI s
(3GdMGOQI gh bWHI Hf ChS Hf eMUf GdZWaGfiTGYQ LGgdis
(3GfXQ ai GdLRA GdChd GdCQbGe (B295-301 (3COH hGdbSe GdKGdK ef GdCQbGe (B1400 1404 (3COHs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B200s
Keywords: (3GdCOHs